PENGARUH LATIHAN VARIASI PUSH UP TERHADAP KEMAMPUAN CHEST PASS SISWA EKSTRAKURIKULER BOLA BASKET DI SMK SETIH SETIO 2 MUARA BUNGO - Deddy Rahmat Saputra (Jurnal Muara Olahraga, 2022)
Abstract Study this background back by lack of strength and accuracy in To do chest pass . Destination study this is for knowing influence the effect of the push up variasit exercise on the ability of the chest pass student extracurricular at SMK Setih Setio 2 Muara Bungo.The method used in this research is the experimental method. the sample amounted to a sample of 16 students. The design used in this research is one group pretest and posttest. The data analysis technique of this research is a hypothesis test (t test) using SPSS Version 0.22The results obtained showed that there was an increase in the chest pass for extracurricular students at SMK Setih Setio with the mean pre-test score of 5.75 and post-test score of 9.88. Statistical analysis using the t test showed a significant value, obtained t count (11.341) > t table (2.13145) was significant so it can be concluded that using push up variant exercises on the chest pass ability of basketball extracurricular students at SMK Setih Setio 2 Muara Bungo. Keywords : push up variations ,chest pass, basketball.